The formation of values with collective productive capabilities: a research agenda pending of the capabilities approach (Mayéutica Revista Científica de Humanidades y Artes, 2024)
This article analyzes, from a sociological perspective, collective productive capabilities as promoters of the structural transformations that developing countries need to reduce poverty, as an alternative to the emphasis on educationand health promoted by Sen’s human capabilities approach. The objective is to answer the question of how values are generated in people, whether it is something only individual or a more social process. The hypothesis that answersthis question is that values are formed mainly with social interrelations. For this, the article is based on the theoretical framework of Berger and Luckmann, and Giddens’ theory of structuring; both theories are applied to the issue of collectiveproductive capabilities, as understood by Andreoni and others. These approaches reinforce the emerging category of collective capabilities, which criticizes the individualistic emphasis of Sen’s capabilities approach. The article concludes that, accepting that human values are formed mainly through social relations will strengthen the idea that it is possible to mobilize people to improve human development in less advanced countries; such social relations can be practiced in various ways, one of which is, as the article assumes, with collective productive capabilities.
Keywords: value formation; collective productive capabilities; capabilities approach; mobilisation; structural transformations